Aerosol-into-liquid capture and detection of atmospheric soluble metals across the gas–liquid interface using Janus-membrane electrodes - Zhao, Yi-Bo; Cen, Tianyu; Jiang, Fuze; He, Weidong; Zhang, Xiaole; Feng, Xiaoxiao; Gao, Min; Ludwig, Christian; Bakker, Eric; Wang, Jing (Proceedings of the National Academy of Sciences - PNAS, 2023)
The soluble fraction of atmospheric transition metals is particularly associated with health effects such as reactive oxygen species compared to total metals. However, direct measurements of the soluble fraction are restricted to sampling and detection units in sequence burdened with a compromise between time resolution and system bulkiness. Here, we propose the concept of aerosol-into-liquid capture and detection, which allowed one-step particle capture and detection via the Janus-membrane electrode at the gas–liquid interface, enabling active enrichment and enhanced mass transport of metal ions. The integrated aerodynamic/electrochemical system was capable of capturing airborne particles with a cutoff size down to 50 nm and detecting Pb(II) with a limit of detection of 95.7 ng. The proposed concept can pave the way for cost-effective and miniaturized systems, for the capture and detection of airborne soluble metals in air quality monitoring, especially for abrupt air pollution events with high airborne metal concentrations (e.g., wildfires and fireworks).